2020
DOI: 10.1002/wdev.375
|View full text |Cite
|
Sign up to set email alerts
|

FOXP transcription factors in vertebrate brain development, function, and disorders

Abstract: FOXP transcription factors are an evolutionarily ancient protein subfamily coordinating the development of several organ systems in the vertebrate body. Association of their genes with neurodevelopmental disorders has sparked particular interest in their expression patterns and functions in the brain. Here, FOXP1, FOXP2, and FOXP4 are expressed in distinct cell type‐specific spatiotemporal patterns in multiple regions, including the cortex, hippocampus, amygdala, basal ganglia, thalamus, and cerebellum. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
100
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(107 citation statements)
references
References 161 publications
(364 reference statements)
7
100
0
Order By: Relevance
“…Importantly, FOXP4 is not only expressed in adult tissue, but also during different stages of development of, e.g., the heart, lungs, gut, and skeleton, where it has been shown to play important functional roles. 2,[32][33][34][35] This widespread expression pattern, in combination with the large number of transcriptional targets and protein-protein interactions known for FOXP transcription factors, 10,[36][37][38] could potentially yield a large variety of downstream consequences when FOXP4 functions are compromised. It is thus not surprising that we found a broad range of associated phenotypes in individuals with likely pathogenic FOXP4 variants, including growth deficits, developmental delays and a spectrum of associated congenital abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, FOXP4 is not only expressed in adult tissue, but also during different stages of development of, e.g., the heart, lungs, gut, and skeleton, where it has been shown to play important functional roles. 2,[32][33][34][35] This widespread expression pattern, in combination with the large number of transcriptional targets and protein-protein interactions known for FOXP transcription factors, 10,[36][37][38] could potentially yield a large variety of downstream consequences when FOXP4 functions are compromised. It is thus not surprising that we found a broad range of associated phenotypes in individuals with likely pathogenic FOXP4 variants, including growth deficits, developmental delays and a spectrum of associated congenital abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, in FOXP1and FOXP2-related disorders, expressive speech problems are a prominent feature, 40 and the contributions of these regulatory factors to the development and function of relevant neural circuits are extensively studied. 10,42 A recent study linking FoxP1/2/4 functions to vocal learning in songbirds suggested that FOXP4 should also be considered as a candidate for involvement in vocal disorders. 43 Indeed, all individuals with likely pathogenic FOXP4 variants in our study had delayed speech/language development, with expressive problems prominently present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the PB provides input to other components of the central complex involved in angular orientation (Kim et al, 2019;Kottler et al, 2019;Seelig and Jayaraman, 2015;Su et al, 2017). (Co et al, 2020;Lu et al, 2002;Shu et al, 2007). What is less well known is if adult FoxP expression serves any specific function.…”
Section: Foxp Expressionmentioning
confidence: 99%
“…In mammals, the FoxP subfamily (FoxP1-4) members (Santos et al, 2011) are abundantly expressed during the development of multiple cell types, such as cardiomyocytes, neurons, lung epithelial secretory cells and T-cells (Golson and Kaestner, 2016). In particular, FoxP1 and FoxP2 have generated interest because of their roles in regulating the development of cognitive processes such as speech and language acquisition (Bolhuis, 2011;Carr et al, 2010;Co et al, 2020;den Hoed and Fisher, 2020;Hagoort, 2019;Horn et al, 2010;Lai et al, 2001;Morgan et al, 2016;Reuter et al, 2017;Schatton and Scharff, 2016).…”
Section: Introductionmentioning
confidence: 99%